Genetic and diet effects on Ppar-α and Ppar-γ signaling pathways in the Berlin Fat Mouse Inbred line with genetic predisposition for obesity - Wagener Asja; Goessling Helge F; Schmitt Armin O; Mauel Susanne; Gruber Achim D; Reinhardt Richard; Brockmann Gudrun A (Lipids in Health and Disease, 2010)
Abstract Background The Berlin Fat Mouse Inbred (BFMI) line is a new mouse model for obesity, which was long-term selected for high fatness. Peroxisome proliferator-activated receptors (PPARs) are involved in the control of energy homeostasis, nutrient metabolism and cell proliferation. Here, we studied the expression patterns of the different Ppar genes and the genes in the PPAR pathway in the BFMI line in comparison to physiological changes. Results At the age of 10 weeks, the BFMI mice exhibited marked obesity with enlarged adipocytes and high serum triglycerides concentrations in comparison to the often used mouse line C57BL/6 (B6). Between these two lines, gene expression analyses revealed differentially expressed genes belonging to the PPAR pathway, in particular genes of the lipogenesis and the fatty acid transport. Conclusion Surprisingly, the Ppar-α gene expression was up-regulated in liver and Ppar-γ gene expression was down-regulated in the white adipose tissue, indicating the activation of a mechanism that counteracts the rise of obesity.